ORDER OF THE MAIN PARTS OF SPEECH IN UZBEK AND ENGLISH LANGUAGES - Hojieva Rukhsatbegim Tuymurod qizi; Bannopova Zulxumor Xatamovna (Journal of new century innovations, 2023)
Introduction: Everyone pays attention not to the grammatical structure or word order, but to the short and concise statement of the point he wants to make. But the order of sentences is important in expressing an idea. In unnecessary cases, changing the positions of sentence parts can have a positive or negative effect on the meaning of the sentence, as a result, some additional meanings may appear in the sentence or spelling and stylistic errors may occur. Therefore, it is appropriate to learn a foreign language in comparison with the mother tongue.